PulseRider Treated Aneurysm with Significant Artifact on Postoperative Magnetic Resonance Angiography: A Case Report and Literature Review - Anthony V. Nguyen; Laura K. Reed; Walter S. Lesley (Neurointervention, 2021)
The PulseRider is a neuroendovascular adjunct for wide-necked intracranial aneurysms. The decreased metal burden of the PulseRider theoretically reduces artifact on radiologic imaging. However, we report here on a case of a patient who underwent PulseRider-assisted stent-coiling of a basilar tip aneurysm. He returned 19 months later for intermittent diplopia and darkening of vision but was neurologically intact on exam. Both contrast-enhanced and time-of-flight magnetic resonance angiography (MRA) demonstrated absence of signal in the basilar artery in the proximal anchors of the PulseRider. Given his lack of reproducible symptoms and high functional status, it is presumed that the imaging reflected artifact and not thrombosis/stenosis. Although the PulseRider is a useful treatment option for wide-necked intracranial aneurysms, the clinician should be aware that even contrast-enhanced MRA can produce artifact that resembles thrombosis/stenosis. Non-angiogram radiologic imaging modalities may be appropriate for evaluation for residual aneurysm but not patency of the parent artery.